Unitech Webstore Computer Sales and Services - Muniandy, Dinesh; HASAN BASARI, ABD SAMAD (Applied Information Technology And Computer Science, 2025)
The Unitech Webstore system is a web-based solution that improves the online visibility and operational efficiency of Unitech Smart IT Solutions. The technology addresses critical issues such as limited internet access, manual appointment scheduling, and inefficient order tracking. It includes an integrated product catalog, seamless order administration, secure payment processing, and a repair scheduling purpose. Customers may easily explore items, track orders, and schedule repair appointments, which reduces in-store congestion and improves overall service quality. The system uses a systematic development strategy to ensure usability, dependability, and smooth functionality through thorough user acceptability testing. Unitech Webstore is designed to be versatile and adaptive, with the goal of modernizing the shopping experience by providing a seamless digital platform for both customers and administrators. This project is expected to drive business growth, enhance customer satisfaction, and position Unitech Smart IT Solution as a competitive player in the digital marketplace.